Ultrasonic monitoring of actively and passively protected RC structures - Sharma, Ashutosh (My University, 2013)
One of the major causes of catastrophic failures in reinforced concrete structures such as bridges, dams and buildings is the deterioration of reinforcing bars due to corrosion. If the degradation remains unnoticed inside concrete, it further accelerates and causes huge loss of life and property. Removal of concrete to visually inspect the reinforcement is detrimental to the structure. Hence, it is imperative to develop a non-intrusive health monitoring technique for early detection of corrosion related damages in steel embedded in concrete. Guided ultrasonic waves offer a potentially attractive solution. In the present study, bars embedded in concrete are subjected to corrosion and also protected with FRP‘s (CFRP and GFRP). These materials have received gr eat attention and their applications to structural repair and retrofit have grown significantly in recent years. CFRP and GFRP fabrics are largely employed because it offers superior performance such as resistance to corrosion, high stiffness - to-weight ratio, high tensile strength, light weight, high durability and easy installation etc. These protected specimens are monitored ultrasonically using longitudinal guided waves. A mode with minimal attenuation and mode shape that is suitable for detection of a particular type of damage is chosen from dispersion curves. For this purpose, we conduct the Pulse Echo Investigations . The reinforcements have been excited at one end only with an ultrasonic pulse using piezoelectric transducer which acts as the transmitter and the receiver itself Ultrasonic testing is carried out on bars in concrete by simulating corrosion in the form of area loss and delamination. It is observed that corrosion of reinforcing bars in concrete is discernible using ultrasonic guided waves. This thesis investigates the efficacy of ultrasonic guided waves in picking up the behavior of RC Structures when subjected to corrosion and also after protection.
Master of Engineering-Structural
Keywords: Ultrasonic; Active protection; Passive Protection; Guided Waves